Does Pre-Acclimation Enhance the Tolerance of Quercus ilex and Arbutus unedo Seedlings to Drought? - Angela Balzano; Chiara Amitrano; Carmen Arena; Antonio Pannico; Rosanna Caputo; Maks Merela; Chiara Cirillo; Veronica De Micco (Plants)
Mediterranean forests are severely threatened by increasing seedling mortality due to harsh environmental conditions, especially drought. In this study, we investigate whether seedlings of Quercus ilex and Arbutus unedo, previously exposed to water deficit, acquired tolerance to summer drought. Seedlings of the two species were grown from April to September in a plastic tunnel greenhouse and exposed to two irrigation regimes (control, 100% water holding capacity; water-stressed, 50% of control). In mid-August, the irrigation of all plants was suspended for three weeks. The response of the species was analyzed to evaluate survival, growth, ecological, and anatomical traits of wood produced under stressful conditions and marked through the pinning technique. The results suggest that both species show pre-acclimation to drought, with Q. ilex demonstrating a marked increase in survival percentage. This is likely due to a reduction in vessel size in response to previous water stress. In contrast, in A. unedo, the higher frequency of narrower vessels allowed safer water transport compared to Q. ilex, thus explaining the slight increase in survival. Overall results indicated that the two species adopt different strategies to overcome drought, providing valuable insights for managing seedlings in natural ecosystems and urban green spaces.